Malawi : Third and Fourth Reviews Under the Extended Credit Facility Arrangement, Request for Waivers for Non-observance of Performance Criteria, Extension of the Arrangement, Rephasing of Disbursements, and Modification of Performance Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report, 2014)
This Supplement Information focuses on recent developments regarding the Malawi government's response to the recent fiscal scandal and on the implementation of two remaining prior actions. The IMF staff welcomes the continued progress in implementing remedial actions to address the recent fraud and actions by the authorities toward meeting the end-December 2013 quantitative targets. The IMF staff also welcomes the interim forensic audit report. Although it did not contain all the information sought by the IMF staff, it had enough to assure the IMF staff that the remedial measures being implemented by the authorities to strengthen system controls and financial management are in the right areas. Some risks remain. It will be important to cautiously implement the fiscal spending program to preserve buffers, lest the final audit reveal slightly larger fund misappropriation.